"Moral Law Within": The Morality of the Enslaved in Three American Novels - Loomis, Jennifer L. (My University, 2008)
Scholarly work on slave literature has often focused on the immorality of white slaveholders, but slavery presented its most profound challenge, perhaps, to those who were actually enslaved. As a step toward recognizing the complicated human relationships created by the institution of slavery and acknowledging the full, complex humanity of the enslaved, this thesis examines the ethical dilemmas facing slaves as represented in Harriet Beecher Stowe's Uncle Tom's Cabin (1852), Octavia E. Butler's Kindred (1979), and James McEachin's Tell Me a Tale: A Novel of the Old South (1996). These novels cover the spectrum of possible ethical responses to enslavement, ranging from refusing to harm a master to killing whites in retaliation for the abuses of slavery. Because authors often address their own ethical concerns through the plight of their slave characters in complex and interesting ways, the study of both nineteenth- and twentieth-century literature dealing with slavery allows readers and critics to explore how writers represent fictional slaves in ways that engage not just the morality of slaveholding but also other ethical concerns of their societies. Writing immediately after the passage of the Fugitive Slave Law, Stowe creates Uncle Tom as a moral model for her white middle-class readers. Writing in response to the Black Power Movement of the 1960s and 1970s, Butler avers that misrepresentations of the past distort the realities of slavery and the ethical courage that it took to survive enslavement. McEachin, responding to the court cases involving Rodney King and O. J. Simpson in the 1990s, challenges readers to consider the ethical implications of storytelling and asserts that before the United States can overcome its racial divisions, Americans must learn to tell the truth about their past.
Thesis submitted in partial fulfillment of the requirements for the degree of Master of Arts -- English.
Keywords: race relations in literature, American fiction, African American authors, ethics in literature, slavery in literature